Relationship between organizational characteristics and information security knowledge management implementation - Said, Abd Rahman; Abdullah, Haslinda; Uli, Jegak; Mohamed, Zainal Abidin (Elsevier, 2014)
The main objective of this paper is to empirically examine the effects of organizational characteristics and its dimensions, culture, top management support, reward and incentive, and organization structure as knowledge management success factor on information security knowledge management implementation. Using the quantitative analytical approach, the theoretical model and hypotheses in this study were fully tested based on the empirical data collected from 182 services sector in Malaysia and most importantly, those companies are registered with the Registrar Companies of Malaysia (ROC). Data gathered from the survey questionnaires were then analyzed using the correlation coefficients and multiple linear regression analyses. The results showed that organizational characteristics made significant positive effects. The results were in-line and consistent with previous studies on knowledge management development. The study has connected the literature gaps by providing empirical evidence on the effects of knowledge management success factors on information security knowledge management implementation.